Conceptualising spaced learning in health professions education: A scoping review. Issue 3 (20th December 2019) - Versteeg, Marjolein; Hendriks, Renée A.; Thomas, Aliki; Ommering, Belinda W. C.; Steendijk, Paul
Abstract: Objectives: To investigate the definitions and applications of 'spaced learning' and to propose future directions for advancing its study and practice in health professions education. Method: The authors searched five online databases for articles published on spaced learning in health professions education prior to February 2018. Two researchers independently screened articles for eligibility with set inclusion criteria. They extracted and analysed key data using both quantitative and qualitative methods. Results: Of the 2972 records retrieved, 120 articles were included in the review. More than 90% of these articles were published in the last 10 years. The definition of spaced learning varied widely and was often not theoretically grounded. Spaced learning was applied in distinct contexts, including online learning, simulation training and classroom settings. There was a large variety of spacing formats, ranging from dispersion of information or practice on a single day, to intervals lasting several months. Generally, spaced learning was implemented in practice or testing phases and rarely during teaching. Conclusions: Spaced learning is infrequently and poorly defined in the health professions education literature. We propose a comprehensive definition of spaced learning and emphasise that detailed descriptions of spacing formats are needed in future research to facilitate the operationalisation of spaced learning research and practice in health professions education. Abstract : Digging into the educationally strategic phenomenon of spaced learning, the authors discover variety that leads them to propose a comprehensive definition and emphasise that detailed format descriptions are needed to facilitate further development.